HANDPHONE SEBAGAI KENDALI BEBAN LISTRIK MELALUI SHORT MASSAGE SERVICE BERBASIS MIKROKONTROLER AT89S52 - Damsi, Faisal (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTThis instrument controller represent an appliance used a easier human being in order to in doing work repeatedly for example animating put-on or put-off the light wireless by using handphone. This appliance aim to know problem relatedto control system and design a control system which can be used indoor of doorstep so that earn easier turn off and turn on by using handphone. With this control system existence is easier one can to fire and put-off the light though thethe people there no at home. At this lamp controller used by a device conduct, device mikrokontroller, device relay burden and and also the relay device. At device conduct used by handphone receiver and consignor, at device microcontroller used by IC AT89S52 where program used by is Proview 32 hence can be programed a delivery order automatically to receiver target number without having to turn off and turn on or animate its in the manual. Measurement done by using voltmeter multimeter or. At measuring load electric through relay as ON/OFF where Microcontroller AT89C52 to active load electric that output port will be logic 0 volt that to no active load electric that ouput port will be 5 volt.Keywords : Hand Phone, Short massage service, Relay